2017
DOI: 10.3892/ijo.2017.4079
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin effectively inhibits the malignant phenotypes of uveal melanoma cells by targeting NF-κB pathway

Abstract: Uveal melanoma (UM) is a highly aggressive intraocular malignancy that lacks any effective targeted-therapy. Neither survival nor prognosis has been improved for the past decades in patients with metastatic UM. NF‑κB pathway is reported to be abnormally activated in UM. However, the role of NF‑κB pathway as a potential therapeutical target in UM remains unclear. Here, the effect of pristimerin, a potent inhibitor of NF‑κB pathway, on UM cells in terms of growth, apoptosis, motility, invasion and cancer stem-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Also, NF-κB pathway has been implicated in the pathogenesis of malignant melanoma. It was reported some medicines realized the melanoma-inhibiting effect through inactivating NF-κB pathway [24,44]. Previous studies have shown that activation of NF-κB can inhibit apoptosis induced by a number of stimuli [45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, NF-κB pathway has been implicated in the pathogenesis of malignant melanoma. It was reported some medicines realized the melanoma-inhibiting effect through inactivating NF-κB pathway [24,44]. Previous studies have shown that activation of NF-κB can inhibit apoptosis induced by a number of stimuli [45].…”
Section: Discussionmentioning
confidence: 99%
“…18 2.8 | Cell cycle analysis by flow cytometry EC9706 and EC109 cells were seeded in 6-well plates and treated with or without pristimerin for 48 hours. 18 2.8 | Cell cycle analysis by flow cytometry EC9706 and EC109 cells were seeded in 6-well plates and treated with or without pristimerin for 48 hours.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…18,25 EC9706 and EC109 cells were incubated with (2.0 μM) or without pristimerin for 24 hours, and the ALDH + cells were detected by flow cytometry. 18,25 EC9706 and EC109 cells were incubated with (2.0 μM) or without pristimerin for 24 hours, and the ALDH + cells were detected by flow cytometry.…”
Section: Pristimerin Attenuates the Properties Of Cancer Stem-like mentioning
confidence: 99%
See 2 more Smart Citations